If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25h = 20h + 15 Reorder the terms: 25h = 15 + 20h Solving 25h = 15 + 20h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-20h' to each side of the equation. 25h + -20h = 15 + 20h + -20h Combine like terms: 25h + -20h = 5h 5h = 15 + 20h + -20h Combine like terms: 20h + -20h = 0 5h = 15 + 0 5h = 15 Divide each side by '5'. h = 3 Simplifying h = 3
| 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 | | 3(2t^2-5)=t | | -5x+-5=9x | | a^2x^2-8abx+16b^2=0 | | 97-4x=41x+17 | | 9=a(14) | | 11-10x=40-17x | | 10x+35=28x+35 | | -74-9x=7x+22 | | 8p-24+10p=138 | | 19r=304 | | 2x+10=-20-8x | | 9a=14 | | 3x-4-x=2x-4 | | r-17=20 | | 124-6x=2x+20 | | 2x+(4x+1)=15 | | 3x-8=0 | | 28+2n=14 | | -9x+15=-22-4(x+22) | | 2x+7(.5)=2 | | 10+8x=4x+16 | | 12h=156 | | -3-6x=6-7x | | 4h(2+6h)= | | 8x^2+33x-35= |